Craniospinal space reduction and malalignment due to atlas assimilation in Basilar Invagination–A case–control study - Ricardo V. Botelho; Beatriz Cibin Braga Petranchi; Pedro B. Botelho; Diego U.M. Moreira; Eduardo F. Bertolini; José M. Rotta (World Neurosurgery: X)
Introduction: Type I Basilar invagination is associated with the assimilation of the anterior arch of the atlas. Observation suggests that the assimilation of the atlas does not allow the development of the normal space between the skull and C1 and displaces the high cervical spine towards the neural structures, posteriorly positioned. Purpose: The objective of this work is to evaluate craniospinal alignment in patients with type I Basilar invagination and AOA in comparison with normal subjects (Type I). Methods: Magnetic resonance images and / or CT SCAN with reconstruction in the midline, in acquisitions at t1 and or t2, from 30 normal subjects and 27 patients with type I Basilar invagination were evaluated. The position of Anterior arch of Atlas and odontoid process in relation to the Basion and distances between C1 and C2 to the anterior border of foramen magnum were compared between groups. Results: The distance from C2 to the Basion was significantly higher in the BI group than in the control group (t test: t = 4.18; p = 0) and the space between the skull and Atlas was reduced. All normal subjects had the Atlas anteriorly located in relation to the Basion. In AOA, all patients had Atlas in line with or posteriorly dislocated in relation to the Basion and the Odontoid process occupying the foramen magnum space. Conclusion: data revealed that AOA prevents a normal position of skull in relation to the Atlas and a presumed “slip-back” cranio-spinal displacement during developmental period.